2021
DOI: 10.1182/hematology.2021000298
|View full text |Cite|
|
Sign up to set email alerts
|

COVID-19 and thrombosis: searching for evidence

Abstract: Early in the pandemic, COVID-19-related increases in rates of venous and arterial thromboembolism were seen. Many observational studies suggested a benefit of prophylactic anticoagulation for hospitalized patients using various dosing strategies. Randomized trials were initiated to compare the efficacy of these different options in acutely ill and critically ill inpatients as the concept of immune-mediated inflammatory microthrombosis emerged. We present a case-based review of how we approach thromboembolic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 38 publications
0
12
0
1
Order By: Relevance
“…It is well known now that contracting the novel coronavirus disease 2019 (COVID‐19) represents a significant hypercoagulable risk factor for VTE development, particularly in hospitalized patients with moderate and severe forms of COVID‐19 29 . The development of acute PE/VTE associated with or complicated by COVID‐19 represents a unique and challenging clinical scenario.…”
Section: Role Of Perts During the Covid‐19 Pandemicmentioning
confidence: 99%
“…It is well known now that contracting the novel coronavirus disease 2019 (COVID‐19) represents a significant hypercoagulable risk factor for VTE development, particularly in hospitalized patients with moderate and severe forms of COVID‐19 29 . The development of acute PE/VTE associated with or complicated by COVID‐19 represents a unique and challenging clinical scenario.…”
Section: Role Of Perts During the Covid‐19 Pandemicmentioning
confidence: 99%
“…Platelet hyperreactivity, which could result from direct viral invasion or indirect activation by cytokine release, and activation of the complement system may cause further cytokine release, stimulating the coagulation cascade and suppressing fibrinolysis. Additionally, patients with severe COVID-19 may have limited mobility, which promotes vascular stasis, platelet and erythrocyte aggregation, and thrombosis ( 9 ).…”
Section: Pathophysiology Of Sars-cov-2 Infectionmentioning
confidence: 99%
“…Thromboembolism may involve numerous organ systems. In addition to small vessel thrombosis, which is one of the hallmarks in autopsies of COVID-19 patients with respiratory and multisystem organ failure, large vessel venous thromboembolism is also common ( 9 ). Deep venous thrombosis (DVT) occurs in about 20%–25% of hospitalized patients and may result in pulmonary embolism ( 37 ).…”
Section: Covid-19 In Msk Systemmentioning
confidence: 99%
“…It has been suggested that the polyanionic constituents of the adenovirus vector-based vaccines trigger antibody production against PF4 (platelet factor 4) which, in turn, induce platelet activation. As a result, thrombocytopenia and thrombosis occur [63].…”
Section: Covid-19 Vaccine-induced Immune Thrombocytopenic Purpuramentioning
confidence: 99%